ENHANCING TRANSPARENCY AND ENGAGEMENT: THE ROLE OF E-GOVERNMENT INITIATIVES IN FOSTERING INCLUSIVE GOVERNANCE IN THE DIGITAL AGE - Chuangkrai, Rachata (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the transformative impact of e-government initiatives on transparency and public engagement, emphasizing their role in fostering inclusive governance in the digital era. Method: Employing a qualitative approach, the study synthesizes case examples and literature on ICT-enabled governance tools, including digital identity systems, participatory platforms, and AI analytics. Results: The findings reveal that e-government platforms significantly enhance transparency by providing real-time access to public data and facilitate inclusive participation through user-centered design and interactive forums. Successful implementations, such as Estonia’s digital identity, Rwanda’s Irembo, and South Korea’s participatory budgeting, demonstrate increased accountability and trust in public institutions. However, persistent challenges—such as digital inequality, institutional inertia, and cybersecurity risks—must be addressed. Novelty: This paper offers a comprehensive, comparative analysis of innovative e-government practices and argues for strategic, inclusive, and secure adoption pathways. By highlighting diverse global implementations and their outcomes, it contributes to a deeper understanding of how digital governance can reinforce democratic processes and inform future research focused on long-term effectiveness and scalability.